Pengaruh Tax Amnesty dan E-Filing pada Kepatuhan Wajib Pajak Orang Pribadi di Kabupaten Badung - Putra, I Nyoman Toni Artana; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
Issues concerning tax compliance are important because non-tax compliance will simultaneously lead to tax avoidance efforts, resulting in reduced deposits of tax funds to the state coffers. In order for the taxpayer compliance level to increase, it is necessary to note the factors that influence taxpayer compliance. The purpose of this study is to determine the effect of tax amnesty and e-filing on taxpayer compliance. This research was conducted in Badung regency with its population is all individual taxpayer in Badung regency. The number of samples in this study as many as 100 respondents, with sampling method used is accidental sampling. Based on the results of the analysis, tax amnesty and e-filing simultaneously have a significant effect on the taxpayer compliance of individuals. The results of this study also indicate that tax amnesty and e-filing partially have a positive and significant effect on the taxpayer compliance of individuals. Keywords : Compliance, Tax Amnesty, e-Filing